PENENTUAN KADAR RESIDU PESTISIDA PROFENOFOS PADA TANAMAN TOMAT GAFHA DENGAN METODE GAS CHROMATOGRAPHY - Futeri, Renny (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2023)
Research on determination of Profenofos Pesticide Residue Levels on Agafha Tomatoes Using Gas Chromatography Method has been carried out. The purpose of conducting research on samples of tomatoes that are often consumed by the community is to find out whether the tomato plants are suitable for consumption by the community or whether they have a negative impact if consumed frequently and to find out whether the tomato samples reach the maximum residue limit that has been set. After analyzing the Agaftha tomato samples in the pesticide laboratory, data was obtained that the Agaftha tomatoes contained prefenofos pesticide residues with a concentration of 0.0805 mg/kg, and the results of this test stated that the Agaftha tomato samples could be consumed properly because the concentration did not exceed the maximum residue limit. Prefenofos residue is regulated in the Regulation of the Minister of Agriculture of the Republic of Indonesia Number 55/PERMENTAN/KR.040/11/2015. The maximum residue limit (BMR) for the active ingredient profenofos is 10 mg/Kg. Hence, it can be concluded that the Agaftha tomato sample is suitable for consumption because the concentration of residue levels in the Agaftha tomato sample is lower than the BMR which has been regulated in the Regulation of the Minister of Agriculture of the Republic of Indonesia.